Built-in Misdirection: On the Difficulties of Learning to Knap. (2nd January 2019) - Lycett, Stephen J.; Eren, Metin I.
ABSTRACT: Flintknappers must successfully deploy specific physical techniques to make stone artifacts. Somewhat analogous to flintknapping, the successful performance of conjuring tricks also relies on effective deployment of physical actions and techniques to bring about desired outcomes. To prevent spectators detecting the cause–effect relationships between these physical actions, conjurors use various forms of "misdirection." Recently, there has been intensified academic interest in misdirection by experimental psychologists and cognitive scientists. Here, we show that misdirection provides a valuable model for examining the cognitively challenging elements of learning to knap through observation. Several implications arise from conceiving of these issues in terms of their capacity for "misdirection." This includes the possibility of connecting them with well-understood psychological mechanisms, especially those underpinning the cognition of accurate perception, attention, memory, and reasoning. This can open novel avenues of enquiry relating to social learning, the evolution of technological "complexity, " and for connecting archaeology with cognitive neuroscience.